EKRANISASI NOVEL 172 DAY KARYA NADZIRA SYAFA KE FILM 172 DAY SUTRADARA HADRAH DAENG RATU - Wulan, Suci; Wardiah, Dessy; Rukiyah, Siti (Parataksis: Jurnal Bahasa, Sastra, dan Pembelajaran Bahasa Indonesia, 2025)
This research is titled the expansion of the novel 172 Day by Nadzira Syafa to the film 172 Day directed by Hadrah Daeng Ratu. This study aims to describe the aspects of shrinkage, addition and variation in the novel 172 Day by Nadzira Syafa to the film 172 Day directed by Hadrah Daeng Ratu. The data sources in this study are the novel 172 Day by Nadzira Syafa and the film 172 Day directed by Hadrah Daeng Ratu. The method used in this study is a qualitative descriptive method. The data collection technique in this study is document techniques, both writings, drawings and other works. The data validity technique in this study is the triangulation technique. This research produces several aspects of shrinkage, expansion and variation aspects. The shrinkage aspect in this study has 3 characters and 1 setting. The additional aspects of this research are 3 figures and 6 settings. There are 6 different aspects of the change in the flow of this research. The conclusion of this study is that there are aspects of shrinkage, addition and change that vary from the novel 172 day to the movie 172 day.